Distribución espacio-temporal de la contaminación del agua del río chumbao andahuaylas, apurímac, Perú. 2011-2012 - Torres García, Luz Azucena (2016)
Conditions Chumbao river pollution were evaluated. This was taken into account by characterizing hydrological, physical, chemical and biological factors and the determination of water quality indices. The study area comprised the fluvial sector from Ccoyahuacho (Jeronimo Saint) to Posoccoy (Talavera). The Chapman longitudinal profile (1998) was applied as well as the Rickert synoptic approach (1998) and Canter methodology (1998) to estimate water quality within a space-temporal analysis. The sampling sites were chosen taking into account previous observation of changes in ecosystem areas, wastewater discharges -point and non-point sources of pollution-, hydrological context, resources use, physical accessibility, synoptic research. Some "in situ" parameters were measured and the others were analyzed in the laboratory of Biotechnology of the Universidad Nacional de José María Arguedas. The parameter fecal coliform index presented lower quality and pH the higher as the temperature. The indices of water quality indicators are appropriate for Chumbao river pollution, as an instrument for identifying the deterioration or improvement of a body of a stream water. In general, the gradient of hydrological, physical, chemical and biological characteristics recorded showed serious environmental deterioration of Chumbao river pollution. A strong upward trend in the concentrations and amounts of the various parameters in the three sampling events from the CH-05 to the downstream station CH-10 was observed.